Implementation of Bioentrepreneurship Learning Using Comics to Improve Creative Thinking Skill on the Sub Concepts of Angiosperms for High School Students - Putri, Yuliana (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Bioenterpreneurship learning by using comics is one of the contextual learning and can train creative thinking skill students. Therefore this study aims to determine the creative thinking skill students of bioentrepreneurship learning using comics. This research is a quantitative study with a quasi-experimental method of non-equivalent pretest-posttest control group design. The instruments used for data collection include observation sheets, pre-test post-test, and student response questionnaires. The results showed that the creative thinking skill abilities of the experimental class students improved better than the control class and the responses of students in the experimental class were included in the strong criteria. Based on the results of the study it can be concluded that learning bioenterprenership using comics increase creative thinking skill abilities students